Analysis by Fourier transform infrared spectroscopy of Johnstonia (Corystospermales, Corystospermaceae) cuticles and compressions from the Triassic of Cacheuta, Mendoza, Argentina (Ameghiniana, 2013)
Abstract. Spectroscopic information (functional groups and semi-quantitative data) of corystosperm cuticles and compressions from the Triassic of Cacheuta, Mendoza, Argentina, is reported for the first time. Fossil leaves of Johnstonia spp. (Corystospermales, Corystospermaceae) were analyzed by Fourier transform infrared spectroscopy (FT-IR) in an attempt to identify spectroscopic patterns that would characterize these taxa. Infrared spectra obtained from cuticles and compressions of Johnstonia spp. showed a relatively rich aliphaticstructure as well as hydroxyl, carbonyl and some other oxygen-containing functional groups. Semi-quantitative data derived from FT-IR spectra were statistically analyzed using one-way analysis of variance test (ANOVA). In the three taxa studied herein, one-way ANOVA revealed significant differences between cuticles andtheir corresponding compressions regarding the CH2/CH3 ratio (p < 0.05). Considering the FT-IR-derived ratios CH2/CH3, Al/Ox, Ox1/Ox2 and C-H/C=O, there were not significant differences (p > 0.05) between abaxial and adaxial surfaces in the cuticular samples of Johnstonia coriacea var. coriacea (Johnston) Walkom here studied. Infrared-derived ratios here considered (CH2/CH3, Al/Ox and Ar/Al) in compression samples did not differ significantly from one taxon to the other (p > 0.05). However, cuticular specimens of Johnstonia spp. showed statistical differences (p < 0.05) among the taxa studied, considering CH2/CH3, Ox1/Ox2 and C-H/C=O ratios. Although these results are suggestive of the likely application of FT-IR technique to the chemotaxonomic study of the Corystospermaceae, more data are needed before obtaining definitive conclusions.Resumen. ANÁLISIS POR ESPECTROCOSPÍA DE INFRARROJO CON TRANSFORMADA DE FOURIER DE CUTÍCULAS Y COMPRESIONES DE JOHNSTONIA (CORYSTOSPERMALES CORYSTOSPERMACEAE) DEL TRIÁSICO DE CACHEUTA, MENDOZA, ARGENTINA. Por primera vez se da a conocer información espectroscópica (grupos funcionales y datos semicuantitativos) de cutículas y compresiones de corystospermas del Triásico de Cacheuta, Mendoza, Argentina. Utilizando espectroscopia infrarroja con transformada de Fourier (IR-TF), se analizaron hojas fósiles de Johnstonia spp. (Corystospermales, Corystospermaceae) en un intento por identificar patrones espectroscópicos que caracterizarían a estos taxones. Los espectros de infrarrojo obtenidos de cutículas y compresiones de Johnstonia spp. mostraron una estructura alifática relativamente rica como así también hidroxilos, carbonilos y otros grupos funcionales que contienen oxígeno. Los datos semi-cuantitativos derivados de espectros de IR-TF fueron analizados estadísticamente utilizando el test de análisis de la varianza de un factor (ANOVA). En los tres taxones aquí estudiados y considerando la relación CH2/CH3, ANOVA de un factor reveló diferencias significativas entre cutículas y sus correspondientes compresiones (p < 0.05). Respecto a las relaciones CH2/CH3, Al/Ox, Ox1/Ox2 y C-H/C=O, no hubo diferencias significativas (p > 0.05) entre las superficies abaxial y adaxial de las cutículas de Johnstonia coriacea var. coriacea (Johnston) Walkom aquí estudiadas. Las relaciones CH2/CH3, Al/Ox y Ar/Al consideradas en compresiones no difirieron significativamente de un taxón a otro (p > 0.05). Sin embargo, las cutículas de Johnstonia spp. mostraron diferencias estadísticas (p < 0.05) entre los taxones estudiados, considerando las relaciones CH2/CH3, Ox1/Ox2 y C-H/C=O. Aunque estos resultados parecen indicar la posible aplicación de la técnica de IR-TF al estudio quimiotaxonómico de las Corystospermaceae, se requieren más datos antes de obtener conclusiones definitivas.